Catalytic binary oxides decorated zeolite as a remedy for As(III) polluted groundwater: Synergistic effects and mechanistic analysis. Issue 2 (April 2023) - Angaru, Ganesh Kumar Reddy; Lingamdinne, Lakshmi Prasanna; Choi, Yu-Lim; Koduru, Janardhan Reddy; Chang, Yoon-Young
Abstract: Inexpensively composites derived from industrial waste products are being extensively researched in water treatment, particularly in arsenic removal, to acquire safe water resources. Here, it is reported that a cheap and effective composite of marigold-flowered structured iron-manganese binary oxide decorated fly ash zeolite for efficient removal of As(III) from water, is fabricated using a two-step hydrothermal approach. Arsenite ions [As(III)] are highly harmful, soluble, mobile, and more challenging to eliminate from aqueous solution than arsenates [As(V)]. The synthesized composite is amorphous and has a high surface area (243.55 m 2 /g). The Z @ Fe3 O4 –MnO2 binary oxide composite showed a higher As(III) adsorption capacity than those of zeolite-free counterparts, their single-oxide components, and the pristine zeolite, in addition, to efficiently oxidative-adsorption of As(III) by Fe3 O4 –MnO2 system. The zeolite functioned as effective support that prevented aggregation of the oxide nanoparticles and contributed to the synergistic effects exhibited by Z @ Fe3 O4 –MnO2 . The synthesized composite exhibited a maximum As(III)-removal capacity (80 mg/g) that was relatively higher than that competitive with that of most reported sorbents. Moreover, Z @ Fe3 O4 –MnO2 was able to eliminate 100% arsenic from natural groundwater, and the arsenic-loaded Z @ Fe3 O4 –MnO2 can be readily regenerated and repeatedly utilized for up to 4 cycles by maintaining WHO's drinking water standard levels. The overall findings illuminate the effectiveness, feasibility, and reusability of the designed composite for water treatment. Graphical Abstract: ga1 Highlights: The prepared inexpensive, large-surface-area Z @ Fe3 O4 –MnO2 has porous marigold-like structures. Zeolite well functioned and assisted in Z @ Fe3 O4 –MnO2 exhibiting synergistic effects. Factors including pH, thermodynamics, and coexisting ions were investigated. The As(III) oxidative removal mechanism was comprehensively examined. Effective application on real groundwater remediation and reuse up to 4 cycles by satisfying the WHO's standard levels.